Women’s Transformational Leadership in Educational Institutions from A Gender Perspective - Kholifah, Yusnia Binti; Setyoningrum, Muthia Umi (JURNAL AL-TANZIM, 2025)
According to the Global Gender Gap Report 2025 (WEF), gender equality in Indonesia remains unequal globally, although women's roles in public leadership, including education, have been shown to increase institutional presence. However, previous research has not comprehensively analyzed the characteristics of women's transformational leadership. This study aims to examine the characteristics of women's transformational leadership from a gender perspective. The study used a qualitative approach through interviews, documentation, and observation, and analyzed the data using a multi-case study, including individual and cross-case analysis. The results show that the characteristics of women's transformational leadership include idealized influence with feminist role models grounded in religious values, inspirational motivation grounded in development, intellectual stimulation grounded in globalization, and individualized consideration grounded in personal growth. This research contributes to the development of knowledge on transformational leadership from a gender perspective. It provides practical recommendations for women's leadership models and a paradigm shift in gender bias in education.